Supply Chain Management : Securing a Superior Global Edge - Venkataraman, Ray R. (SAGE Publications, Inc. (US), 2022)
Supply Chain Management: Securing a Superior Global Edge takes a holistic, integrated approach to managing supply chains by addressing the critically important areas of globalization, sustainability, and ethics in every chapter. Authors Ray Venkataraman and Ozgun C. Demirag use a wide variety of real-world cases and examples from the manufacturing and service sectors to illustrate innovative supply chain strategies and technologies. With a focus on decision-making and problem-solving, Supply Chain Management provides students with the tools they need to succeed in today’s fiercely competitive, interconnected global economy.